Undisclosed Penitentier in Indonesian Criminal Law Reform - Setyawan*, Vincentius Patria; Widiartana, Gregorius (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The WvS-NI, which was later translated and made into Indonesian criminal law, does not contain cover-up punishment as a form of criminal sanction. Closing punishment is regulated in Law Number 20 of 1946 concerning Closing Punishment and was later determined as one of the main crimes in the Old Criminal Code (WvS-NI translation) as an alternative to imprisonment which is intended for crimes with motives that deserve respect. Throughout the history of criminal law enforcement, the criminal sanction of closure has only been applied 1 (one) time, namely in the 3 July Affair, and has never been applied since then. Nevertheless, the reform of criminal law in Law Number 1 of 2023 concerning the Criminal Code still maintains cover-up punishment as one of the main crimes. This article will discuss related to the regulation of criminal cover-ups in the renewal of criminal law.